Ureteropelvic junction obstruction in infants: Open or minimally invasive surgery? A systematic review and meta-analysis - Cascini, Valentina; Lauriti, Giuseppe; Di Renzo, Dacia; Miscia, Maria Enrica; Lisi, Gabriele (Frontiers in Pediatrics, 2022)
IINTRODUCTION The historical gold standard treatment for uretero-pelvic junction obstruction (UPJO) was the open Anderson-Hynes dismembered pyeloplasty (OP). Minimally Invasive Surgery (MIS), including Laparoscopic Pyeloplasty (LP) and Robot-assisted Laparoscopic Pyeloplasty (RALP), have been reported to achieve better outcomes (i.e. decreased morbidity, reduced postoperative pain, superior esthetic results, and shortened length of hospital stay, LOS), with a success rate similar to OP. The main limit to MIS approach is the age and weight of patients, preferring to limit these procedures to children >1 year. The aim of the study is to evaluate the feasibility and the benefits of MIS pyeloplasty compared to OP to surgically treat UPJO in children <1 year of age. MATERIAS AND METHODS A systematic review was independently performed by two authors. Those papers comparing both techniques (MIS pyeloplasty versus OP) in infants were included in the meta-analysis. Data (mean±DS or percentage) were analyzed using Rev.Man 5.4 A p<0.05 was considered significant. RESULTS Nine studies (8 retrospective, 1 prospective) meet the inclusion criteria. A total of 3,145 pyeloplasties have been included, with 2,859 (90.9%) OP and 286 (9.1%) MIS. Age at operation was 4.91.4 months in OP versus 5.82.2 months for MIS, p=ns. Weight at surgery was 6.41.4 Kg in OP versus 6.91.4 Kg in MIS, p=ns. Operative time was 129.424.1 minutes for OP versus 144.032.3 minutes in MIS, p<0.001. LOS was 3.21.9 days for OP versus 2.20.9 days for MIS, p<0.01. Post-operative complications were present in 10.012.9% of OP versus 10.911.6% of MIS, p=ns. Failure of surgery was 5.23.5% for OP versus 4.23.3% for MIS, p=ns. CONCLUSION The development of miniaturized instrument and technical modifications has made MIS feasible and safe in infants and smaller children. MIS presented longer operative time than OP. However, MIS seemed effective for the treatment of UPJO in infants, showing shortened LOS compared to OP. No differences have been reported with regards incidence of post-operative complications and failure of pyeloplasty. Given the low quality of evidence of the meta-analysis according to the GRADE methodology, we would suggest to limit MIS procedures in infant only in those high-volume centers with experienced surgeons.